From Political to Economic Awakening in the Arab World : The Path of Economic Integration - Chauffour, Jean-Pierre (Washington, DC: World Bank, 2013)
The forces unleashed by the Arab political awakening have the power to be transformational. One critical parameter of success will be whether the Arab political awakening is accompanied by a concurrent economic awakening. Such an economic awakening would need to generate quality employment for the millions of young men and women who are looking for jobs and a decent life. In most Arab countries, it has become evident that the development paradigm of the past cannot achieve the qualitative and inclusive growth expected by the population. Economic integration through increased trade and foreign direct investment (FDI) is one key means available to policy makers in the short to medium term to put the Partnership countries on a higher path of sustainable economic growth and in a position to decisively tackle the problem of unemployment, especially youth unemployment. The comprehensiveness of the proposed integration strategy is also designed to facilitate its political feasibility and acceptance. Although any single efficiency-enhancing reform may hurt a particular group or individual, once it is part of a broad and comprehensive reform agenda, the potential negative effects of reform tend to cancel out each other, making everyone a winner.